Safety assessment of statin-drug interaction effects in cardiology outpatient in Teaching Hospital at Surabaya: Penilaian keamanan efek interaksi obat statin pada pasien kardiovaskular rawat jalan RS Pendidikan di Surabaya - Ana Khusnul Faizah; Amitasari Damayanti; Nani Wijayanti Dyah Nurrahman (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: HMG-CoA inhibitors, more commonly known as statins, are lipid-lowering agents that have benefits in cardiovascular therapy. Statins are associated with two significant side effects that are asymptomatic elevations of liver enzymes and myopathy. Myopathy is the most likely to occur when statins are prescribed with other drugs. Objectives: To evaluate the effect of drug interactions between statins and concomitant drugs in outpatient cardiovascular patients. Methods: This study conducted in a prospective cohort. Drug interactions was checked by using lexicomp drug interactions software and patient’s complaints were taken through interviews. Results: There were 69 patients included in this study as sample. A total of 16 patients received atorvastatin, and 53 patients received simvastatin. More than half of sample (59%) showed statin-drug interactions. The most drug interactions were severe (41%), followed by moderate (22%) and mild (10%). The most interacting drugs were amlodipine and diltiazem. Based on the results of interview, there were no complaint of myopathy felt by patient. Conclusion: The effects of drug interactions still need to be considered even though the patients did not complain myopathy. Several factors can determine the impact of drug interactions that is not experienced by the patients.